Design an Earthquake Early Warning System Based on Arduino Uno Microcontroller with Accelerometer-MPU6050 sensor and NodeMCU-ESP8266 - Sianturi, Immanuel Ivan; Hamdani, Dedy; Risdianto, Eko (Universitas Syiah Kuala, 2024)
Geographically, Indonesia is located in three rings of active plates and surrounded by various active mountains that make Indonesia prone to earthquakes. When the earthquake occurred, there were still many people who were late in getting information to carry out the early evacuation process. This research aims to provide solutions to people who are late in receiving earthquake information by developing a microcontroller-based earthquake early warning system alarm with MPU6050 accelerometer sensors and NodeMCU ESP8266 to minimize possible losses. This research uses the Research and Development method with the ADDIE development model, to develop an Arduino uno-based earthquake alarm from previous research. This research uses a literature study system for analysis of earthquake problems when an earthquake occurs. The results of this study are in the form of a tool equipped with an Arduino Uno microcontroller system, where the earthquake warning system is run according to the system design. The tools developed were validated by three expert lecturers using validation questionnaires. Data analysis was carried out quantitatively to determine the feasibility of Arduino-based earthquake early warning tools using the Likert scale. Based on the average results of validation tests by experts, 91% of earthquake early warning tools developed are in the very decent category. Based on the trials carried out, the tool can provide warnings to the public directly